Seismic Performance of Embedded Column Base Connections with Attached Reinforcement: Tests and Strength Models - Hassan, Ahmad S.; Kanvinde, Amit M. (Engineering Journal, 2023)
Embedded column base (ECB) connections used in mid- to high-rise steel moment frames derive moment resistance through bearing of the embedded column and base plate against the concrete footing. Five large-scale tests on ECB connections are presented; these feature cantilever columns subjected to axial compression and cyclic lateral loading. The tests feature reinforcement details including (1) horizontal reinforcement bars attached to the column (either directly welded to the flanges or in the form of U-hairpins wrapped around the column); and (2) vertical reinforcement in the form of stirrups in the footing. These tests complement previous experiments that are nominally identical but without the additional reinforcement. The tests indicate that while the horizontal reinforcement enhances moment strength due to resisting forces in the horizontal direction, it also produces a tension field that decreases the restraint to the rotation of the embedded base plate, ultimately reducing overall moment strength. The addition of vertical reinforcement in the form of stirrups mitigates this issue to an extent. A strength model considering these effects is proposed and shown to predict strength with good accuracy across a range of configurations, encompassing the different configurations of horizontal and vertical reinforcement. Limitations of the approach are discussed.